United Europe and Euclidean Pluralism On the Anthropological Paradox of Contemporary EU Legal Experience - Ricca, Mario (UNIO – EU Law Journal, 2015)
The European Union was born under the sign of ‘unity in diversity’ and pluralism. Such a design with its rather oxymoronic combination of ends has so far found an institutional and procedural synthesis. From a cultural point of view, however, Europe is divided, and efforts towards anthropological translation, at least in as reflected by the law, have so far been very scant. This diffraction results in a legal pluralism that addresses the national cultures as if they were parallel entities and, just like in a Euclidean universe, doomed never to meet. This essay aims at opening a pathway to develop a European legal interculture, as an outcome of both anthropological-spatial understanding – chorology – and legal experience aligned with the needs of European citizens and amenable to support the project of a Europe whose ‘unity’ may no longer consist of reciprocal cultural indifference. A Europe that no longer shares a common space of justice but rather, precisely, shares an interspace of a common justice.